2013
DOI: 10.1155/2013/417894
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis of Adjuvant Therapy after Potentially Curative Treatment for Hepatocellular Carcinoma

Abstract: Adjuvant IFN therapy can improve both RFS and OS; however, the benefits of using this agent should be weighed against its side effects. Combination of systemic and transhepatic arterial chemotherapy is not recommended for HCC after potentially curative treatment. Other adjuvant therapies produce limited success for survival. Additional RCTs with proper design are required to establish the role of adjuvant therapies for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 74 publications
(269 reference statements)
0
40
0
Order By: Relevance
“…Sorafenib administration (HR Th e safety and effi cacy of both Sorafenib alone and combined Sorafenib plus TACE has also been demonstrated for patients with advanced HCC ( 12,(14)(15)(16)(17)(18)33 ). A recent, more relevant, study by Li et al ( 15 ) evaluated the safety of Sorafenib plus TACE-RFA for palliative treatment in a limited number of patients with unresected HCC.…”
Section: Prognostic Factors For Os and Tumor Recurrencementioning
confidence: 99%
See 1 more Smart Citation
“…Sorafenib administration (HR Th e safety and effi cacy of both Sorafenib alone and combined Sorafenib plus TACE has also been demonstrated for patients with advanced HCC ( 12,(14)(15)(16)(17)(18)33 ). A recent, more relevant, study by Li et al ( 15 ) evaluated the safety of Sorafenib plus TACE-RFA for palliative treatment in a limited number of patients with unresected HCC.…”
Section: Prognostic Factors For Os and Tumor Recurrencementioning
confidence: 99%
“…Retrospective and randomized studies have suggested that the combined use of Sorafenib, TACE, and RFA may be useful in patients with unresectable HCC ( 12,(14)(15)(16)(17)(18). Based on these information and the multiple actions of Sorafenib, we hypothesized that Sorafenib plus RFA (Sorafenib-RFA) may be useful in patients with early HCC or recurrent HCC.…”
Section: Introductionmentioning
confidence: 99%
“…19 In endometrial cancer, HPSE1 was associated with lymph node metastasis, deep myometrial invasion, angiolymphatic invasion, and high-grade tumors. 20Y22 An important role of HPSE1 in carcinogenesis has also been shown.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the proven effect in the palliative setting, adjuvant systemic chemotherapy with sorafenib after liver resection for HCC showed no beneficial effects on recurrence-free survival in the current randomized, double-blind, placebo-controlled STORM-trial (NCT0069277) [32] . However, there are some promising results that interferon might improve overall and recurrence-free survival in the adjuvant setting [33,34] . But interferon therapy is also accompanied by a variety of side effects such as flu-like symptoms, fever, fatigue, myalgia, and cephalgia, which might limit the suitability of this treatment option in many patients.…”
Section: Cryotherapymentioning
confidence: 99%